Further evidence in favour of a carbanion mechanism for glycolate oxidase. Issue 5 (27th March 2023) - Pasquier, Hélène; Lederer, Florence
Abstract : The flavoenzyme glycolate oxidase oxidizes glycolic acid to glyoxylate and the latter, more slowly, to oxalate. It is a member of an FMN‐dependent enzyme family that oxidizes l ‐2‐hydroxy acids to keto acids. There has been a controversy concerning the chemical mechanism of substrate oxidation by these enzymes. Do they proceed by hydride transfer, as observed for NAD‐dependent enzymes, or by initial formation of a carbanion that transfers the electrons to the flavin? The present work describes a comparison of the reactivity of glycolate, lactate and trifluorolactate with recombinant human glycolate oxidase, by means of rapid‐kinetics experiments in anaerobiosis. We show that trifluorolactate is a substrate for glycolate oxidase, whereas it is known as an inhibitor for NAD‐dependent enzymes, as is trifluoroethanol for NAD‐dependent alcohol dehydrogenases. Unexpectedly, it was observed that, once reduced, a flavin transfers an electron to an oxidized flavin, so that the end species is a flavin semiquinone, whatever the substrate. This phenomenon has not previously been described for a glycolate oxidase. Altogether, considering that another member of this flavoenzyme family (flavocytochrome b 2, a lactate dehydrogenase) has also been shown to oxidize trifluorolactate (Lederer F et al. (2016) Biochim Biophys Acta 1864, 1215–21), this work provides another important piece of evidence which is hardly compatible with a hydride transfer mechanism for this flavoenzyme family. Abstract : It is shown that trifluorolactate is a substrate for glycolate oxidase. Flavin reduction by trifluorolactate is a mechanistic proof for the intermediate formation of a carbanion. Surprisingly, for glycolate, lactate and trifluorolactate, the reduction end product is a flavin semiquinone. Global analysis of the flavin reduction kinetics suggests an inter‐tetramer electron transfer.